Analysis of Factors Affecting the Intention to Revisit Domestic Tourists to Lombok Utara Regency - Satriani Dwi Putri; Junaidi Sagir; Rusminah HS; L Adi Permadi (Tinta Emas Institute, 2023)
Nusa Tenggara Barat also has a variety of tourist destinations in each district and city, one of which is Lombok Utara Regency. This study aims to analyze the factors that influence the intention of domestic tourists to visit Lombok Utara Regency again. The sampling technique in this study used purposive sampling. The population in this study were tourists who had visited North Lombok Regency. The sample in this study were 100 respondents. The analysis technique used is Factor Analysis. The results of the factor analysis test can be concluded that the factors that influence the intention to revisit domestic tourists to North Lombok Regency formed 7 factors in which there are 36 variables with a variance of 73, 992%. The eight factors are the factors of Tourist Attractions, Promotion, Security, Facilities, Prices, Culture and Accessibility. The dominant factor is the Tourist Attraction factor with a variance value of 47.911% and the smallest factor is Accessibility with a variance of 28.50%.